Patient perceptions of nurse mentors facilitating the Aussie Heart Guide: A home‐based cardiac rehabilitation programme for rural patients. Issue 1 (4th October 2015) - Frohmader, Terence John; Lin, Frances; Chaboyer, Wendy
Abstract: Aim: To explore and describe long‐term thoughts and perceptions of the Aussie Heart Guide Programme including the role of the mentor, held by patients recovering from myocardial infarction. Design: A qualitative design. Methods: Thirteen patients recovering from myocardial infarction who were unable to attend a hospital‐based or affiliated outpatient cardiac rehabilitation programme were interviewed by telephone at the completion of the programme and asked to describe the relationship with their assigned nurse mentor and their perception of the audiovisual used in the programme. Results: Three themes emerged; assisting me to cope, supporting me and my family and tailoring the programme to my needs. Patients were satisfied with the programme and appreciative of the supportive and caring relationships provided by mentors during their hospitalization through to their discharge from the programme.